2006
DOI: 10.1177/197140090601900205
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Foetal MRI in Studying the Germinal Matrix: Comparison with Autopsy

Abstract: Our study aimed to combine in vivo foetal cerebral magnetic resonance findings and histopathological analysis to chart details of the development and characteristics of the germinal matrix not disclosed by ultrasound, and to establish standard normal parameters for in vivo investigation. We enrolled pregnant women between the 18th and 23rd weeks of gestation awaiting voluntary termination of pregnancy. The patients had a foetal cerebral magnetic resonance scan and the aborted foetus subsequently underwent auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The indirect evidence for antenatal MRI showed that six studies favoured the index test in a previable population 64 67 69 113 160 166. However, in another six studies, autopsy was favourable,116 129 133 143 146 152 and one study presented a 50:50 split between agreement and disagreement 65…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The indirect evidence for antenatal MRI showed that six studies favoured the index test in a previable population 64 67 69 113 160 166. However, in another six studies, autopsy was favourable,116 129 133 143 146 152 and one study presented a 50:50 split between agreement and disagreement 65…”
Section: Resultsmentioning
confidence: 99%
“…However this only amounted to 54 studies in total as some artices described different tests from the same study. Of the 134 indirect evidence papers or abstracts, 133 were synthesised41–174 as well as a single trial record 175. None of the seven included trials identified from trial registries reported interim or final results and only four remain active 176–179.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation